A neurological presentation of intravascular B-cell lymphoma. (3rd August 2012) - Kendall, Kimberley Marie; Thomas, Rhys H; Corkill, Robin G; Robertson, Neil P
Abstract : Intravascular B-cell lymphoma is a rare, aggressive subtype of diffuse large B-cell lymphoma that presents insidiously with symptoms relating to organ involvement. We present the case of a male in his late 40s who presented with fluctuating neurological symptoms including episodes of altered upper-limb sensation, seizures and psychotic phenomena. These symptoms and signs were associated with fleeting brain lesions on neuroimaging. A brain biopsy confirmed the diagnosis of intravascular B-cell lymphoma and he was treated with CHOP chemotherapy (cyclophosphamide, hydroxydaunorubicin, vincristine and prednisolone). Two years later, he remains well. Timely diagnosis and aggressive treatment provides an optimal chance of long-term survival so it is essential to recognise early disease characteristics.